Recent plant-synthesized gold nanoparticle advancements for gastric cancer therapy - Marco A. Rojas-Cessa (Nano TransMed)
Gastric cancer is the fifth most common form of cancer across the globe, according to the latest WHO GLOBO-CAN 2022 report. Metal nanoparticles (MNPs) have been attracting attention for cancer therapy due to the many advantages they provide compared to traditional cancer treatment drug delivery systems. Specifically, gold nanoparticles (AuNPs) are potentially advantageous for clinical applications because of their biocompatibility and their application in biomedical imaging. A drawback of AuNPs is that their synthesis is typically very hazardous and produces a lot of toxic byproducts. However, the green synthesis of AuNPs overcomes this issue by using natural and biological derivatives (from microorganisms, fungi, plants, etc.). This allows for a safer and less toxic procedure, while maintaining the reliability and reproducibility of AuNP synthesis. Plant-synthesized AuNPs (PAuNPs) in particular present a greatly efficient and fast method for AuNP synthesis, due to the presence of reducing agents and capping agents in plant extracts to support the nucleation and formation of AuNPs. Herein, we review existing literature to summarize recent in vitro and in vivo developments of PAuNPs against gastric cancer. Categorization of the reviewed literature includes their physiochemical characterization, cytotoxic IC50’s against gastric cancer cell lines, methods of gastric cancer cell death, and the change in relevant biomarker expressions due to PAuNP presence. A generalized gastric cancer cell death mechanism is concluded, which stems from the endocytotic uptake of PAuNPs that eventually leads to mitochondria dysfunction, nuclear fragmentation, autophagy expression alteration, apoptosis, and/or ferroptosis. Although in vivo developments for PAuNPs against gastric cancer are limited, studies have indicated PAuNPs’ ability to cause angiogenesis inhibition and tumor size reduction. The discussion includes comments on remaining challenges and additional work for the pre-clinical development of PAuNPs against gastric cancer.